Physicochemical properties, mechanism of action of lycopene and its application in poultry and ruminant production - Long, Yong; Paengkoum, Siwaporn; Lu, Shengyong; Niu, Xinran; Thongpea, Sorasak; Taethaisong, Nittaya; Han, Yong; Paengkoum, Pramote (Frontiers in Veterinary Science, 2024)
Lycopene is a kind of natural carotenoid that could achieve antioxidant, anti-cancer, lipid-lowering and immune-improving effects by up-regulating or down-regulating genes related to antioxidant, anti-cancer, lipid-lowering and immunity. Furthermore, lycopene is natural, pollution-free, and has no toxic side effects. The application of lycopene in animal production has shown that it could improve livestock production performance, slaughter performance, immunity, antioxidant capacity, intestinal health, and meat quality. Therefore, lycopene as a new type of feed additive, has broader application prospects in many antibiotic-forbidden environments. This article serves as a reference for the use of lycopene as a health feed additive in animal production by going over its physical and chemical characteristics, antioxidant, lipid-lowering, anti-cancer, and application in animal production.